Pengembangan Lembar Kerja Peserta Didik Sekolah Dasar Model Problem Based Learning Berbasis Kearifan Lokal Sasak - Sobri, Muhammad; Handika, Ilham; Fauzi, Asri (Primera Educatia Mandalika: Elementary Education Journal, 2025)
The purpose of this study is to develop a Problem-Based Learning (PBL) model worksheet (LKPD) based on Sasak local wisdom. The researcher also aims to determine the validity and practicality of the developed LKPD. In this study, the product developed is a PBL model LKPD based on Sasak local wisdom. The development model used is the ADDIE model, which includes analyze, define, development, implementation, and evaluation. The LKPD product is considered valid if it meets the validity criteria based on the assessments of expert validators. Furthermore, the LKPD product is considered practical if it meets the practicality criteria based on teacher responses. Based on the results and discussions described above, the conclusions of this study are: first, the development procedure of this research consists of three stages: analysis, design, and development. Second, the assessment results from two expert lecturers indicate that the PBL LKPD based on local wisdom is feasible and ready for trial use. The assessment from the two expert lecturers scored 74.5 out of a maximum score of 95, or 78%, which is qualitatively classified as valid. Therefore, the quality of the development product in the form of a PBL LKPD based on Sasak local wisdom is deemed suitable for trial use. A small group trial was then conducted to assess the practicality of the developed LKPD. The trial results showed that the teacher assessment questionnaire scored 69 or 73%, which falls into the practical category.